Cross-sectional study on knowledge, attitude and prevalence of domestic violence among women in Kaduna, north-western Nigeria. Issue 3 (8th March 2022) - Nmadu, Awawu Grace; Jafaru, Abubakar; Dahiru, Tukur; Joshua, Istifanus Anekoson; Nwankwo, Bilkisu; Mohammed-Durosinlorun, Amina
Abstract : Background: Domestic violence is a global issue of public health concern with detrimental effects on women's physical, mental and social well-being. There is a paucity of community-based studies assessing the knowledge and attitude of women towards domestic violence in Nigeria. Objective: To assess knowledge, attitudes, prevalence and associated factors of domestic violence among women in a community in Kaduna, Nigeria. Design: A descriptive cross-sectional study. Setting: A selected community in Kaduna South Local Government Area in Kaduna State. Participants: In total, 170 women aged 15–49 years participated in the study. Primary and secondary outcome measures: The outcomes were knowledge, attitude and prevalence of domestic violence. Results: The mean age of the respondents was 28.7+7.9 years. A total of 113 (66.5%) respondents had high level of knowledge about domestic violence with 114 (67.1%) having non-tolerant attitudes towards domestic violence. The lifetime prevalence and 12-month prevalence of domestic violence were 47.1% and 35.3%, respectively. The results of logistic regression identified the educational status of women as a significant predictor of knowledge of domestic violence (adjusted OR (aOR)=0.32; 95% CI 0.15 to 0.68), while marital status (aOR=0.21; 95% CI 0.05 to 0.96), occupation of women (aOR=2.49; 95% CI 1.13 to 5.49), their tolerance of wife beating (aOR=0.33; 95% CI 0.15 to 0.72) and their partners' consumption habit of alcohol/substance use (aOR=7.91; 95% CI 3.09 to 20.27) were identified as significant predictors of the women's experience of domestic violence. Conclusion: Domestic violence was relatively high among women. Though a majority had high level of knowledge about domestic violence, a significant third had tolerant attitudes towards it. Appropriate health interventions need to be implemented by governmental and relevant stakeholders to target negative attitudes and address associated factors of domestic violence against women.